Complementary Absorbing Star‐Shaped Small Molecules for the Preparation of Ternary Cascade Energy Structures in Organic Photovoltaic Cells. (23rd October 2012) - Cha, Hyojung; Chung, Dae Sung; Bae, Suk Young; Lee, Min‐Jung; An, Tae Kyu; Hwang, Jihun; Kim, Kyung Hwan; Kim, Yun‐Hi; Choi, Dong Hoon; Park, Chan Eon
Abstract Two anthracene‐based star‐shaped conjugated small molecules, 5′, 5″‐(9, 10‐bis((4‐hexylphenyl)ethynyl)anthracene‐2, 6‐diyl)bis(5‐hexyl‐2, 2′‐bithiophene), HBantHBT, and 5′, 5″‐(9, 10‐bis(phenylethynyl)anthracene‐2, 6‐diyl)bis(5‐hexyl‐2, 2′‐bithiophene), BantHBT, are used as electron‐cascade donor materials by incorporating them into organic photovoltaic cells prepared using a poly((5, 5‐E‐alpha‐((2‐thienyl)methylene)‐2‐thiopheneacetonitrile)‐alt‐2, 6‐[(1, 5‐didecyloxy)naphthalene])) (PBTADN):[6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC71BM) blend. The small molecules penetrate the PBTADN:PC71BM blend layer to yield complementary absorption spectra through appropriate energy level alignment and optimal domain sizes for charge carrier transfer. A high short‐circuit current (JSC) and fill factor (FF) are obtained using solar cells prepared with the ternary blend. The highest photovoltaic performance of the PBTADN:BantHBT:PC71BM blend solar cells is characterized by a JSC of 11.0 mA cm−2, an open circuit voltage (VOC) of 0.91 V, a FF of 56.4%, and a power conversion efficiency (PCE) of 5.6% under AM1.5G illumination (with a high intensity of 100 mW−2). The effects of the small molecules on the ternary blend are investigated by comparison with the traditional poly(3‐hexylthiophene) (P3HT):[6, 6]‐phenyl‐C61‐butyric acid methyl ester (PC61BM) system.